Presidential Decree-law No. 201 of the Year 2014 On Amending Some Provisions of the Income Tax Law Promulgated By Law No. 91 Of The Year 2005 = قرار رئيس جمهورية مصر العربية بالقانون رقم 201 لسنة 2014 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.